ACHIEVING SDG 3 IN AFRICA: THE ROLE OF INSTITUTIONS, THE ENVIRONMENT, AND SOCIOECONOMIC FACTORS - Alimi, Olorunfemi Yasiru; Oyeku, Bonuola Victoria; Bolarinwa, Fatimah Ololade (Economic Annals, 2025)
With the year 2030 rapidly approaching, most African nations are facing difficulties meeting their sustainable development goal (SDG) commitments. “Good health and well-being”, as outlined in SDG 3, continue to be high on the agenda of nations around the world. A number of factors, including weak institutions, deteriorating environmental conditions, and socioeconomic challenges, among others, have contributed to the difficulties that many sub-Saharan African (SSA) countries face in reaching SDG 3. This study therefore analyses the role of institutions and environmental and socioeconomic factors in achieving good health and wellbeing of 45 SSA nations from 1996 to 2018. Three estimators, pooled OLS, fixed effects, and system GMM, form the basis of our empirical findings. Our finding shows that human outcomes were negatively impacted by the deteriorating environmental quality. Furthermore, weak institutional frameworks explain the region’s poor health outcomes. Concerning the socioeconomic factors, there is substantial statistical evidence linking rising income to better health outcomes. The region’s health status improves once literacy and basic school enrolment increases. Furthermore, investing in infrastructure improves health outcomes through better energy and sanitation. Macroeconomic stability measured by low inflation and net official development assistance improves health outcomes. However, population growth and urbanisation contribute to SSA’s poor health outcomes. The findings provide input into formulating sound health policies for attaining SDG 3.